Successful Stock Signals for Traders and Portfolio Managers : Integrating Technical Analysis with Fundamentals to Improve Performance. - Lloyd, Tom K. (Wiley, 2013)
A comprehensive guide to technical analysis for both the novice and the professional Technical analysis is a vital tool for any trader, asset manager, or investor who wants to earn top returns. Successful Stock Signals for Traders and Portfolio Managers lets you combine technical analysis and fundamental analysis using existing technical signals to improve your investing performance. Author Tom Lloyd Sr. explains all the technical indicators you need to know, including moving averages, relative strength, support and resistance, sell and buy signals, candlesticks, point and figu.